Coronavirus neologisms in the media discourse The case of English-and Russian-language content - Linok, Larisa; Antonova, Irina; Ozeren, Mehmet; Korotaeva, Larisa (Berghahn Journals, 2025)
This article analyses neologisms reflecting the realities of the COVID-19 pandemic in the English and Russian media discourse. Media discourse is currently the main platform for the emergence, testing and entry of new lexical units into the active vocabulary of languages. The research methodology includes content analysis and a continuous sampling method for selecting linguistic material, methods of structural and word formation analysis, comparative analysis, and semantic component analysis. The material for the study was English-and Russian-language web content from Great Britain, Germany, India, China, Russia, the USA and Estonia. The analysis of the neologisms that arose under the influence of the pandemic in terms of word formation demonstrated that in English and Russian the most productive models are addition and blending. Suffixation and clipping are models specific to the Russian language.
Keywords: compounding; coronavirus; derivation model; media language; phraseology